2023
DOI: 10.3390/plants12122279
|View full text |Cite
|
Sign up to set email alerts
|

Water Metabolism of Lonicera japonica and Parthenocissus quinquefolia in Response to Heterogeneous Simulated Rock Outcrop Habitats

Abstract: The karst carbon sink caused by rock outcrops results in enrichment of the bicarbonate in soil, affecting the physiological process of plants in an all-round way. Water is the basis of plant growth and metabolic activities. In heterogeneous rock outcrop habitats, the impact of bicarbonate enrichment on the intracellular water metabolism of plant leaf is still unclear, which needs to be revealed. In this paper, the Lonicera japonica and Parthenocissus quinquefolia plants were selected as experimental materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In addition, the rocks cover a great proportion of the surface area, and those rocks hinder soil layer continuity and reduce the use efficiency and productivity of the land [47][48][49]. Despite these factors, evidence still shows that the funneling effect of rock outcrops is expected to change the distribution pattern of rainwater and help alleviate the problem of crop water stress in karst farmland with scarce water resources [9,23,37]. Therefore, it is necessary to retain the rainwater intercepted by the rock outcrops to the maximum extent through film-mulched rock outcrops, as implemented in this study, which can effectively improve the soil water content of karst farmland and the utilization efficiency of precipitation by crops.…”
Section: Implication Of Film-mulched Rock Outcropsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the rocks cover a great proportion of the surface area, and those rocks hinder soil layer continuity and reduce the use efficiency and productivity of the land [47][48][49]. Despite these factors, evidence still shows that the funneling effect of rock outcrops is expected to change the distribution pattern of rainwater and help alleviate the problem of crop water stress in karst farmland with scarce water resources [9,23,37]. Therefore, it is necessary to retain the rainwater intercepted by the rock outcrops to the maximum extent through film-mulched rock outcrops, as implemented in this study, which can effectively improve the soil water content of karst farmland and the utilization efficiency of precipitation by crops.…”
Section: Implication Of Film-mulched Rock Outcropsmentioning
confidence: 99%
“…The infiltration process and redistribution of rainwater in rocky karst environments are strongly affected by rock outcrops [8,22,23]. The rocks extend from the surface to the underlying bedrock and will strongly induce the vertical infiltration of soil water and then inevitably reduce the soil's water-holding capacity due to their role in accelerating the conversion of surface water and groundwater [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 Zhao et al found that a simulated karst drought reduced the intracellular water-holding capacity and water transfer rate of plants and improved the water utilization efficiency of Lonicera japonica and Parthenocissus quinquefolia . 24 More and more scholars are applying plant electrical parameters to the study of the water metabolism of plants. 23 , 25 However, it is still unclear how the intracellular and extracellular water in tea trees coordinate under water deficit, which remains to be revealed.…”
Section: Introductionmentioning
confidence: 99%